Functional independence measure in patients with intermittent claudication - Caroline Shihara de Assis; Letícia de Carvalho Batista; Nelson Wolosker; Antonio Eduardo Zerati; Rita de Cassia Gengo e Silva (SciELO, 2015)
AbstractOBJECTIVEOf this study were to evaluate the functional independence of patients with intermittent claudication and to verify its association with sociodemographic and clinical variables, walking ability and physical activity level.METHODThis was a descriptive, exploratory, cross-sectional study with a quantitative approach. Fifty participants (66.4 years; 68% male) were recruited from Claudication Unit of a tertiary hospital. Functional Independence Measure were used to evaluate functional incapacity; the Baltimore Activity Scale, to estimate the physical activity level and the Walking Impairement Questionnaire, the walking ability.RESULTSParticipants had complete functional independence (124.8 + 2.0), low levels of physical activity (4.2 + 2.0), and impairment of walking ability; the worst performance was found in walking velocity domain (21.2 + 16.4). The functional independence score was associated with physical activity (r=0,402) and walking ability scores (distance, r=0,485; speed, r=0,463; stairs, r=0,337).CONCLUSIONIn conclusion, the level of functionality is associated with functional capacity in these patients.